Penerapan Arsitektur Bisnis Intelijen Dalam Sistem Informasi E-Commerce - Achmad Fauzi; Dwi Nanda Oktaviani; Ayu Nurjanah M Candra; Julia Veronika; Ilma Diniyah; Faysa Firli Devianti; Zizka Amelia Putri; Alvito Dwi Wangsa (Prisani Cendekia, 2023)
Business Intelligence or commonly abbreviated as BI is a set of business information tangible analysis tools used to unify, search, store and access a lot of data in the context of business processes that lead to making decisions and actions with the aim of improving business or business performance. The method used is qualitative and literature study where the sources used as references are Google Schoolar and other online media. The results of this study show how the application of BI architecture in e-commerce information systems. BI architecture allows the transformation of raw data from consumers of e-commerce stores into knowledge. The knowledge obtained with this architecture has the main purpose of improving the relationship between the company and the customer and improving the management of the company's internal processes.